Strengthening the mosque-based community economy in Cirebon City - Edy Chandra; Amelia Dwi Handayani; Istiqomah Istiqomah (Community Empowerment, 2022)
Mosques serve as places of worship as well as community empowerment, social services, educational opportunities, and boosting local economies. The economic development of mosques in Cirebon City is carried out by utilizing their potential, such as religious, culinary, and cultural tourism. This program aims to discover the potentials of 22 mosques in the city of Cirebon. The method of community service uses ABCD (Asset-Based Community Development). As a result of this program, the 20 mosques taking part in the workshop can determine their potential, including home-based businesses/crafts, stalls outside the mosque, income from infaq, and majelis ta'lim as the potential to establish a Cooperative of Jamaah Masjid (KOPJAMAS).